Flexural behavior of a composite steel and precast concrete open web dissymmetric framing system. (1st November 2019) - Bandelt, Matthew J.; Gross, Shawn P.; Dinehart, David W.; Yost, Joseph Robert; Pudleiner, Joshua D.
Highlights: Flexural behavior of composite open web dissymmetric framing system explored. Response is characterized through full- and component-scale experiments. Structural behavior compared among experiments, code provisions, and mechanics. Recommendations made for design and analysis of innovative framing system. Abstract: The use of composite construction has been incorporated into the design of steel components for decades, creating efficient and stiffer structures through the combined benefits of structural steel and reinforced concrete. Traditional floor systems develop composite action between vertically aligned elements using shear studs or other mechanical transfer elements. In this paper, the behavior of a composite structural system that combines steel beams, precast hollow core slabs, steel reinforcement, and cementitious grout in a unique geometry to create a shallow, monolithic, and composite floor assembly for use in residential and commercial construction is evaluated. Composite action is developed through a linear strain distribution between horizontally aligned concrete slab and steel beam elements. Experimental results from large-scale assembly testing of the composite system, known as the Girder-Slab System, are presented. The sensitivity of the system to material properties and structural geometry is investigated including effective width, section properties, and flexural strength. Comparisons of flexural section properties and strength are made between experimental performance and predictions using mechanics- and code-based principles.